Analysis of vertical jump of first category volley ball players/Análisis del salto vertical de voleibolistas de primera categoría - José Carlos García Bohigas; Yumilka Daisy Ruiz Loaces; Ídolo Gilberto Herrera Delgado (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2021)
The jumping capacity in volleyball is closely linked to the force-speed capacity that players must possess to perform a wide number of jumps during a match. Hence, there are several questions of coaches to get their athletes to reach the top of the elite. The objective of the study presented is to analyze the indicators that influence the vertical jump with countermovement, for the improvement of physical preparation in volleyball player's first category of Havana, to be able to give treatment from the training session. For the acquisition of the data, a strength platform of German origin and the TEMPLO software with its respective Performance Analysis model were used. In this same order, descriptive statistics was applied to the data obtained, and the results are presented through graphs and tables, where the deficiencies in terms of jumping capacity for these players are shown, evidencing the lack of expertise in the transfer from the eccentric phase to the concentric and its result in the success of the game.